Impact of flow and sediment factor selection on downstream channel adjustments in the Lower Jingjiang Reach of the Yangtze River - Tian, Haoyong; Ren, Zaimin; Yao, Chenchen; Zhong, Na; Xia, Chunchen (Frontiers in Environmental Science, 2025)
IntroductionUpstream damming significantly changes the flow and sediment conditions entering downstream reaches, resulting in remarkable channel adjustments. Several response models were applied to analyze the channel adjustments in response to flow and sediment conditions. However, the influence of water surface slope has been underexplored, and there is a lack of comparative analysis between various flow and sediment factors (FSF) and response models.MethodsTo address these gaps, this study compares the effects of different FSFs (water surface slope included) on the dynamic adjustments of the Lower Jingjiang Reach (LJR) by applying two response models.ResultsThe results show that, for the LJR, the combinations of fluvial erosion intensity (the square of the discharge divided by sediment concentration) during the flood season and water surface slope agree well with measured data. Moreover, the factors incorporating the water surface slope consistently outperformed those without it.DiscussionThis study provides valuable insights into selecting flow and sediment factors for response models, enhancing the simulation and prediction of channel adjustments.